2019
DOI: 10.4314/sajas.v48i6.11
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, fatty acid profile and lipid oxidative stability of breast muscle in chickens fed probiotics and antibiotics or their mixture

Abstract: This study assessed the effects of dietary supplementation of probiotics, antibiotics and an antibioticprobiotics mixture on growth performance of broilers, and the fatty acid profile and oxidative stability of broiler breast muscle. A total of 480 one-day-old broiler chicks (Cobb 500) were assigned to four treatment groups and fed for 42 days. The basal diet served as control treatment (Diet 1), while chicks assigned to Diets 2, 3 and 4 were fed the basal diet with the addition of 0.1 mg/kg of an antibiotic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In addition, they are used as feed supplements to improve the performance and antioxidant capacity of animals (Bai et al, 2016b). Recently, the role of probiotics on lipid metabolism has been highlighted, which indicates that the fatty acid composition in poultry meat may be modified by probiotics (Abdulla et al, 2018). In the present study, MDA was determined as an indicator of lipid peroxidation.…”
Section: Effects Of Lactobacillus Reuteri E81 Added Into Rations Of C...mentioning
confidence: 76%
“…In addition, they are used as feed supplements to improve the performance and antioxidant capacity of animals (Bai et al, 2016b). Recently, the role of probiotics on lipid metabolism has been highlighted, which indicates that the fatty acid composition in poultry meat may be modified by probiotics (Abdulla et al, 2018). In the present study, MDA was determined as an indicator of lipid peroxidation.…”
Section: Effects Of Lactobacillus Reuteri E81 Added Into Rations Of C...mentioning
confidence: 76%
“…Bonos et al [94] demonstrated that the fatty acid composition of meat can be altered by microorganisms in the gastrointestinal tract because these microorganisms can hydrogenate USFAs to SFAs. Probiotics could also reduce the oleic acid contents of rat liver [95] and chicken breast [96]. Kalavathy et al [93] revealed that Lactobacillus supplementation of broiler feed does not affect the poly-USFA contents of the chicken meat when compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Although lower feed consumption is observed in some studies, the probiotic allows improvements in other characteristics of greater economic importance such as body weight and feed conversion [53]. Lower feed consumption can be influenced by factors such as heat stress and environments with greater health challenges [54].…”
Section: Challenge Of Replacing Antibiotics With Probioticsmentioning
confidence: 99%